2022
DOI: 10.3389/fmars.2022.906376
|View full text |Cite
|
Sign up to set email alerts
|

Compound Effects of Flood Drivers, Sea Level Rise, and Dredging Protocols on Vessel Navigability and Wetland Inundation Dynamics

Abstract: Maritime transportation is crucial to national economic development as it offers a low-cost, safe, and efficient alternative for movement of freight compared to its land or air counterparts. River and channel dredging protocols are often adopted in many ports and harbors of the world to meet the increasing demand for freight and ensure safe passage of larger vessels. However, such protocols may have unintended adverse consequences on flood risks and functioning of coastal ecosystems and thereby compromising th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…We utilized Delft3D‐FM (Deltares, 2020) as the computational basis to model coastal, fluvial, and pluvial processes in the SNE. Delft3D‐FM is a 2D‐3D hydrodynamic modeling software that is capable of modeling wind, pressure, rain, river flows, surge, and tides on a single model domain and has been applied successfully in past studies of compound flooding (Bakhtyar et al., 2020; Kumbier et al., 2018; Muñoz, Moftakhari, et al., 2022; Muñoz et al., 2020). Delft3D‐FM solves the Navier‐Stokes equations and Boussinesq assumptions for an incompressible fluid in shallow water conditions on an unstructured grid to simulate water velocities and elevations in coastal, riverine, and estuarine systems (Veeramony et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We utilized Delft3D‐FM (Deltares, 2020) as the computational basis to model coastal, fluvial, and pluvial processes in the SNE. Delft3D‐FM is a 2D‐3D hydrodynamic modeling software that is capable of modeling wind, pressure, rain, river flows, surge, and tides on a single model domain and has been applied successfully in past studies of compound flooding (Bakhtyar et al., 2020; Kumbier et al., 2018; Muñoz, Moftakhari, et al., 2022; Muñoz et al., 2020). Delft3D‐FM solves the Navier‐Stokes equations and Boussinesq assumptions for an incompressible fluid in shallow water conditions on an unstructured grid to simulate water velocities and elevations in coastal, riverine, and estuarine systems (Veeramony et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Process‐based numerical models are useful tools to understand the physics of compound flooding in ungauged areas where in situ measurements are missing and provide helpful insights for resilience assessment and planning (Abbaszadeh et al., 2022; Muñoz, Moftakhari, et al., 2022). These methods, however, suffer from various limitations.…”
Section: Coastal Floodmentioning
confidence: 99%
“…Observations from individual estuaries have indicated that dredging can decrease channel roughness, increase tidal amplitudes, enhance depth convergence, decrease flood wave attenuation and reduce tidal dampening and storm surge dampening (Familkhalili et al., 2020; Muñoz et al., 2022; Talke et al., 2021; Talke & Jay, 2020). Capturing this behavior in modeling has proved challenging (Cai et al., 2012), particularly when estuaries are heavily anthropogenically influenced, and move away from classic, width converging estuary morphology, such as in the Rhine‐Meuse Delta (RMD) in The Netherlands (Cox, Lingbeek, et al., 2022) and the Pearl Delta in China (Bao et al., 2022).…”
Section: Introductionmentioning
confidence: 99%